Relationship between microstructure, hardness and corrosion resistance in 20 wt.%Cr, 27 wt.%Cr and 36 wt.%Cr high chromium cast irons - A. Wiengmoon (2018)
The microstructures, hardness and corrosion behavior of high chromium cast irons with 20, 27 and 36 wt.%Cr have been compared. The matrix in as-cast 20 wt.%Cr, 27 wt.%Cr and 36 wt.%Cr high chromium cast irons is pearlite, austenite and ferrite, respectively. The eutectic carbide in all cases is M 7C3 with stoichiometry as (Cr3.37, Fe 3.63)C3, (Cr4.75, Fe2.25)C 3 and (Cr5.55, Fe1.45)C3, respectively. After destabilization at 1000 °C for 4 h followed by forced air cooling, the microstructure of heat-treatable 20 wt.%Cr and 27 wt.%Cr high chromium cast irons consisted of precipitated secondary carbides within a martensite matrix, with the eutectic carbides remaining unchanged. The type of the secondary carbide is M7C3 in 20 wt.%Cr iron, whereas both M23C6 and M7C3 secondary carbides are present in the 27 wt.%Cr high chromium cast iron. The size and volume fraction of the secondary carbides in 20 wt.%Cr high chromium cast iron were higher than for 27 wt.%Cr high chromium cast iron. The hardness of heat-treated 20 wt.%Cr high chromium cast iron was higher than that of heat-treated 27 wt.%Cr high chromium cast iron. Anodic polarisation tests showed that a passive film can form faster in the 27 wt.%Cr high chromium cast iron than in the 20 wt.%Cr high chromium cast iron, and the ferritic matrix in 36 wt.%Cr high chromium cast iron was the most corrosion resistant in that it exhibited a wider passive range and lower current density than the pearlitic or austenitic/martensitic matrices in 20 wt.%Cr and 27 wt.%Cr high chromium cast irons. For both the 20 wt.%Cr and the 27 wt.%Cr high chromium cast irons, destabilization heat treatment gave a slight improvement in corrosion resistance. © 2010 Elsevier B.V. All rights reserved.